Does hospital variation in intrapartum-related perinatal mortality among caesarean births reflect differences in quality of care? Cross-sectional study in 21 hospitals in Burkina Faso. Issue 10 (6th October 2022) - Cavallaro, Francesca L; Kabore, Charles P; Pearson, Rachel; Blackburn, Ruth M; Sobhy, Soha; Betran, Ana Pilar; Ronsmans, Carine; Dumont, Alexandre
Abstract : Objectives: To examine hospital variation in crude and risk-adjusted rates of intrapartum-related perinatal mortality among caesarean births. Design: Secondary analysis of data from the DECIDE (DECIsion for caesarean DElivery) cluster randomised trial postintervention phase. Setting: 21 district and regional hospitals in Burkina Faso. Participants: All 5134 women giving birth by caesarean section in a 6-month period in 2016. Primary outcome measure: Intrapartum-related perinatal mortality (fresh stillbirth or neonatal death within 24 hours of birth). Results: Almost 1 in 10 of 5134 women giving birth by caesarean experienced an intrapartum-related perinatal death. Crude mortality rates varied substantially from 21 to 189 per 1000 between hospitals. Variation was markedly reduced after adjusting for case mix differences (the median OR decreased from 1.9 (95% CI 1.5 to 2.5) to 1.3 (95% CI 1.2 to 1.7)). However, higher and more variable adjusted mortality persisted among hospitals performing fewer caesareans per month. Additionally, adjusting for caesarean care components did not further reduce variation (median OR=1.4 (95% CI 1.2 to 1.8)). Conclusions: There is a high burden of intrapartum-related perinatal deaths among caesarean births in Burkina Faso and sub-Saharan Africa more widely. Variation in adjusted mortality rates indicates likely differences in quality of caesarean care between hospitals, particularly lower volume hospitals. Improving access to and quality of emergency obstetric and newborn care is an important priority for improving survival of babies at birth. Trial registration number: ISRCTN48510263 .